EJERCICIO Nº 6

f ( x) =

3x + 1  3x + 1  2 =  x+2  x+2 

1

f ' ( x) =

1 · 2

1 3 · ( x + 2) − (3x + 1) · 1 · = ( x + 2) 2 3x + 1 x+2

NO PASES A LA SIGUIENTE HOJA HASTA QUE NO HALLAS ENTENDIDO ÉSTA. INTENTA ACABAR EL EJERCICIO ANTES DE VER LA SOLUCIÓN

EJERCICIO Nº 6

f ( x) =

3x + 1  3x + 1  2 =  x+2  x+2 

1

f ' ( x) = 1 · 2

1 3 · ( x + 2) − (3x + 1) · 1 · = ( x + 2) 2 3x + 1 x+2 1 3x + 6 − 3x − 1 · = 3 x + 1 ( x + 2)( x + 2) x+2 1 · 2

NO PASES A LA SIGUIENTE HOJA HASTA QUE NO HALLAS ENTENDIDO ÉSTA. INTENTA ACABAR EL EJERCICIO ANTES DE VER LA SOLUCIÓN

EJERCICIO Nº 6

f ( x) =

3x + 1  3x + 1  2 =  x+2  x+2 

1

f ' ( x) = 1 · 2 1 · 2

1 3 · ( x + 2) − (3x + 1) · 1 · = ( x + 2) 2 3x + 1 x+2 1 3x + 6 − 3x − 1 · = 3 x + 1 ( x + 2)( x + 2) x+2 1 5 · = 3x + 1 x + 2 · x + 2 · ( x + 2) x+2 1 · 2

NO PASES A LA SIGUIENTE HOJA HASTA QUE NO HALLAS ENTENDIDO ÉSTA. INTENTA ACABAR EL EJERCICIO ANTES DE VER LA SOLUCIÓN

EJERCICIO Nº 6

f ( x) =

3x + 1  3x + 1  2 =  x+2  x+2 

1

1 3 · ( x + 2) − (3x + 1) · 1 · = ( x + 2) 2 3x + 1 x+2 1 1 3x + 6 − 3x − 1 · · = 2 ( x + 2)( x + 2) 3x + 1 x+2 1 1 5 · · = 2 3x + 1 x + 2 · x + 2 · ( x + 2) x+2 1 1 5 · · = 2 3x + 1 x + 2 · ( x + 2) f ' ( x) = 1 · 2
NO PASES A LA SIGUIENTE HOJA HASTA QUE NO HALLAS ENTENDIDO ÉSTA. INTENTA ACABAR EL EJERCICIO ANTES DE VER LA SOLUCIÓN

EJERCICIO Nº 6

f ( x) =

3x + 1  3x + 1  2 =  x+2  x+2 

1

f ' ( x) = 1 · 2 1 · 2 1 · 2 2

1 3 · ( x + 2) − (3x + 1) · 1 · = ( x + 2) 2 3x + 1 x+2 1 3x + 6 − 3x − 1 · = 3 x + 1 ( x + 2)( x + 2) x+2 1 5 · = 3x + 1 x + 2 · x + 2 · ( x + 2) x+2 1 5 · = 3x + 1 x + 2 · ( x + 2) 5 (3 x + 1) · ( x + 2) · ( x + 2) 1 · 2

SOLUCIÓN:

f ' ( x) =

5 2 (3 x + 1) · ( x + 2) · ( x + 2)